Case study on access and benefit sharing for non-commercial academic research in Latin America and the Caribbean. Access to Bactris gasipaes, pijuayo, from the national ex situ collection at INIA-Peru: Estudio de caso sobre acceso y distrubucion de beneficios dentro de la investigacion academica no-comercial en America latina y el Caribe. Acceso a Bactris gasipaes pijuayo, de la coleccion nacional ex-situ mantenida en INIA - Ramírez, M.; Zonneveld, Maarten van; Iman, S.; Sigueñas, M. (Diversitas (France), 2014)
The research focused on the biochemical and molecular analysis of 29 accessions from the core collection of Bactris gasipaes (“pijuayo”), maintained at the San Roque INIA Station in Amazonian Peru. The objective is to identify accessions with a wide range of cooking characteristics and variability in nutritional content.